AB1360-HPR A MODEL TO IMPROVE MINORITY PATIENT RECRUITMENT IN LUPUS CLINICAL TRIALS - THE AMERICAN COLLEGE OF RHEUMATOLOGY MIMICT PROJECT EXPERIENCE. (13th June 2020) - Sheikh, S.; Wanty, N.; Mccalla, S.; Santana, A.; Saxena Beem, S.; Walker, J.; Holt, D.; Howell, A.; Holtz, K.; Williams, S.; Anandarajah, A.
Abstract : Background: In the US, African Americans and Latinos are underrepresented in lupus clinical trials (LCTs), 1 despite experiencing the greatest lupus disease burden. 2, 3 Low participation in LCTs results in inadequate data on treatment effectiveness for minority patients, and fewer opportunities for better care and treatment options. 1 Only one percent of minority patients are referred to clinical trials each year. 4 Provider barriers to making referrals include limited time and unfamiliarity with lupus and LCT opportunities. 4 Using US fedral grant funds, the American College of Rheumatology (ACR) developed MIMICT, a two-part model with associated materials to address provider-side LCT referral barriers. The materials include a toolkit for clinical trial sites and an educational toolkit for providers. Objectives: Our objectives are to: Describe the US LCTs disparities. Discuss the research methodology to evaluate the two-part MIMICT model. Assess the feasibility of the model to increase minority involvement in clinical trials. Methods: We designed two studies to evaluate the MIMICT model.The first study used an online, pretest/posttest, two-group evaluation approach to assess the extent to which the educational toolkit increased providers' knowledge, attitudes, self-efficacy, and behavioral intentions to refer minority patients to clinical trial. We conducted the study in 2018 with primary care providers (PCPs) and again in 2019/2020 with speciality providers. The second study used a longitudinal, mised methods, case-study approach to explore the real-world use of the toolkits with clinical trial site teams at two university medical centers. Results: In the first study, among MIMCT-exposed PCPs, mean scores indicated statistical significance at p≤0.001 with more knowledge about referring [55.84 (sd=23.51) vs 41.76 (sd=19.98)], more self-efficacy to refer [55.00 (sd=37.22) vs. 37.99 (sd=34.42)], and more intentions to refer [61.36 (43.85) vs. 33.41 (41.16)] African American patients to LCTs among the treatment group than the control group, respectively. This presentation will discuss additional data comparing the study in 2018 and the study in 2019/2020 and look comparatively at outcomes across provider type. In the second study, we found that the driver for successful engagemetn of providers and their subsequent use of the educational toolkit was the development of a trusting relationship between the clinical trial site teams and providers in the community. The development of trust took repeated and varied modes of contact, which we will discuss in-depth. Conclusion: The MIMICT educational toolkit increase knowledge, self-efficacy, and intentions to refer lupus patients to LCTs. However, building trust between LCT sites and local providers takes time and repeated outreach, but the potential benefits to medicine and minority health are substantial. References: [1]The Society for Women's Health Research. (2011). Dialogues on diversifying clinical trials: successful strategies for engaging women and minorities in clinical trials. Washington, DC: Food and Drug Administration, Office of Women's Health. [2]Falasinnu, T., Chaichian, Y., Bass, M. B., & Simard, J. F. (2018). The representation of gender and race/ethnic groups in randomized clinical trials of individuals with sytemic lupus erythematosus. Current Rheumatology Reports, 20 (4). [3]Pons-Estel, G. J., Alarcon, G. S., Scofield, L., Reinlib, L., & Cooper, G. S. (2010). Understanding the epidemiological progression of systemic lupus erythematosus. Seminars in Arthritis and Rheumatism, 39 (4). [4]Korieth, K. (2016). Engaging healthcare providers as research facilitators. The CenterWatch Monthly, 23, 1-5. Disclosure of Interests: None declared